Genomic surveillance of STEC/EHEC infections in Germany 2020 to 2022 permits insight into virulence gene profiles and novel O-antigen gene clusters - Angelika Fruth; Christina Lang; Tobias Größl; Thomas Garn; Antje Flieger (Elsevier, 2024)
Shiga toxin-producing E. coli (STEC), including the subgroup of enterohemorrhagic E. coli (EHEC), are important bacterial pathogens which cause diarrhea and the severe clinical manifestation hemolytic uremic syndrome (HUS). Genomic surveillance of STEC/EHEC is a state-of-the-art tool to identify infection clusters and to extract markers of circulating clinical strains, such as their virulence and resistance profile for risk assessment and implementation of infection prevention measures. The aim of the study was characterization of the clinical STEC population in Germany for establishment of a reference data set. To that end, from 2020 to 2022 1257 STEC isolates, including 39 of known HUS association, were analyzed and lead to a classification of 30.4 % into 129 infection clusters. Major serogroups in all clinical STEC analyzed were O26, O146, O91, O157, O103, and O145; and in HUS-associated strains were O26, O145, O157, O111, and O80. stx1 was less frequently and stx2 or a combination of stx, eaeA and ehxA were more frequently found in HUS-associated strains. Predominant stx gene subtypes in all STEC strains were stx1a (24 %) and stx2a (21 %) and in HUS-associated strains were mainly stx2a (69 %) and the combination of stx1a and stx2a (12.8 %). Furthermore, two novel O-antigen gene clusters (RKI6 and RKI7) and strains of serovars O45:H2 and O80:H2 showing multidrug resistance were detected. In conclusion, the implemented surveillance tools now allow to comprehensively define the population of clinical STEC strains including those associated with the severe disease manifestation HUS reaching a new surveillance level in Germany.